Vocal and choral performance as an aspect of neuro-education - Rastruba, Tetiana; Dorokhina, Liubov; Konovalova, Iryna; Mykhailets, Viktoriia; Shpak, Halyna; Khomenko, Alla (EduSoft Publishing and Asociatia LUMEN, 2025)
This article is an attempt to understand the human body's reaction to the perception of vocal-choral works. The power of music during vocal and choral performance is that it bypasses the mind and penetrates directly into the soul, brain, and subconscious mind, affecting the human mood. Depending on the content, music can evoke a wide variety of feelings, urges, and desires in a person. It can relax, soothe, revitalise, irritate, etc. There are also such influences that bypass consciousness, settle in the deep structures of our brain, and make up a significant part of our meanings and motives. Undoubtedly, the role of singing and choral singing in the construction of the human “Ego” and its behaviour cannot be overestimated: Our inner world is influenced by many factors, both external and internal. It cannot be denied that they participate in the development of consciousness. Sounds with different frequencies affect a person differently, which is directly related to the rhythms of the brain. The brain receives auditory information through the organs of hearing and analyses it, comparing it with its own rhythms. Each person has their own rhythm with frequency. This is why we have such different musical tastes. Scientific research confirms that vocal and choral singing improves neuroplasticity and promotes attention, memory, and coordination. Singing together also stimulates the production of dopamine and oxytocin, which increases motivation and social interaction. It is important for the development of emotional intelligence and stress tolerance. The article proves the artistic role of vocal-choral singing; it is determined that vocal-choral performance is a powerful tool of neuro-education; the ways of development of vocal-choral performance in neuro-education are investigated; the methods and techniques of development of vocal-choral performance in neuro-education are highlighted.
Keywords: Вокальний перформанс, хоровий перформанс, нейро-освіта